Para que todos sejam um : estudo exegético-teológico de Jo 17,20-26 - Pozzo, Edson Luiz Dal (2006)
May all be one is the affirmation which stimulates our research and reflection. Our purpose is to deepen the subject of unity, in the perspective of John, specifically, the chapter 17 of the Gospel of John. The pos-modern society lives a kind of breaking up in the most varied forms, individual, social, cultural and specifically religious. We are living in a pluralist world. In this pluralist context, there is a question which will be guiding our research. How can we get the unity in a broken up and divided word, how to get the unity? What is the direction of that unity for the mankind? We know that our society car no longer go on, it doesn t carry on well, and we need to find solutions for better way out for the great and the serious crisis which we are facing. It seems that God was moving away of the mankind. The unity of Jesus with the Father and Jesus with the disciples should be a paradox for a society who searches an individual God. This is the purpose. Our research intends to reflect about four points. In the first chapter, in a historical comprehension groups in apposition and in conflict its historical period (a kind of back cloth). In the chapter two, we begin a exegetic study, for which we delimit our perícope de Jo 17, 20-26 in which Jesus mentions the unity for the whole community in the future. Successively we analyze the historical fountains, analysis of the wording, of the literary class and the theological analysis, the strong characteristic of the Gospel of John. At the third chapter, we did our study and exegetic and theological reflection about the contents of our perícope. In this chapter we present two distinct points: the unity and the glory, that they are complemented mutually. In the fourth and last chapter, we try to present a modernization in three dimensions, the first in a personal level, the second in a community sense, and the third, in the level of the society and the creation. After this study, we can conclude that we are before the culminant point of the Christology of John. The joanina community bases itself and characterizes itself through an elevated Christology of being the reason of unity and also of conflict. We have some difficulties to find historical fountains, which characterize the Gospel, but the theological interpretations evidence the activities of Jesus, to remain undefined if it is the evangelist or Jesus who speaks to us. In the interpretation of the context, to be one with the Father show us the attitudes and the actions of Jesus in order of the Father, a kind of submission of the son to the Father. This unity is a model and a prototype for the community of the disciples and the future community. The glory is the divine sense of the unity and the actions of Jesus, the signs are example about that. In the glory, we never find out a complete unity, there is more to be reached, it means o human activity, it means, a grace offered by God. In her we find the transcendent sense of unity, in the present as in the future, being Jesus the time and the place of that transcendence. It cames from the origin of the world and goes until the end. The actualization of the unity, in personal sense reveled itself as our being to God too as our realization being Jesus our prototype and the model of the disciples with Jesus, unity producing fruits being reference to the unity of all christians, no based in the hierarchic order and the institution. May they all be one without bounds of religion, being for ever an internal appeal of every person and every instituicion. Believe in Jesus is to accept the challenge to live the unity with God, with the others and with the creation.